Attitudes and Responses Residents Against Traffic Noise in Malang City, East Java, Indonesia - Ngudi Tjahjono; Imam Hanafi; Latipun Latipun; Suyadi Suyadi (Indonesian Journal of Environment and Sustainable Development, 2020)
Traffic noise that exceeds the required noise level standard in the Minister of Environment Decree No. 48 of 1996 of the Republic of Indonesia can interfere with physiological and psychological health. This research was conducted in the city of Malang, which aims to determine the attitudes and responses of residents who live around the road sections to the noise coming from motorized vehicles that expose it. The study was conducted with interviews assisted with closed and open questionnaires. Simultaneously with the interview, data collection of noise levels outside and inside the house was carried out using a sound level meter. Interviews were conducted between 16:00 and 21:00. Respondents' responses are divided into four variables, namely perception, expectation, attitude, and adjustment to the noise that exposes it. From the separately processed noise level data, it is found that around the road segments in Malang City have far exceeded the required noise level, which is an average of 85.2 dB. From the descriptive analysis obtained facts, respondents have the perception that their place of residence is in a noisy environment. In these conditions, they hope that motor vehicle noise can be reduced or minimized. They are not comfortable living in a noisy environment. There are even some of them who want to move house to a place that is not noisy. Most of them make adjustments to noise with certain treatments. However, quite a number of them did not make any adjustments.